Research on dynamic characteristics and identification method of local defect on the roll surface. (March 2021) - Wu, Shengli; Xing, Wenting; Liu, Ying; Shao, Yimin
Abstract: Local defects are generally produced on the surfaces of roll during long-term work, which not only causes abnormal vibration of the roll mill but also affects the quality of the produced steel strips. In particular, identifying the defects on a well-lubricated roll surface is a challenge. Therefore, a time-varying oil film stiffness model is proposed based on the elastohydrodynamic lubrication theory. A Sendzimir twenty-high roll mill model was developed and combined with the time-varying oil film stiffness model to analyse the vibration characteristics of the roll mill. Simultaneously, a new method for real-time identification of the defect sizes during the rolling process was proposed. Agreement between the simulated and experimental results was used to validate the effectiveness of the proposed model. The changes to the oil film stiffness and roll mill vibration characteristics for different defect sizes on the roll surface are thus analyzed to provide theoretical support for the identification of the local defects.